Migration and human rights: The law as a reinforcer of gendered borders. Issue 4 (December 2019) - Brems, Eva; Peroni, Lourdes; Desmet, Ellen
Borders follow migrants even inside the territory of their State of destination. These 'sticky' figurative borders may flow directly from immigration norms and practice or indirectly from other areas of law. This Special Issue focuses on the gendered nature of these borders, as they rely on/reinforce socially constructed norms of masculinity and femininity. As a result, these figurative borders undermine the equal enjoyment of human rights of migrants, refugees and asylum seekers along gender lines. Specifically, gendered borders are analysed in relation to the themes of asylum, domestic labour and gender-based violence. The human rights of migrants, refugees and asylum seekers in these domains are analysed in an integrated and complex fashion. The analysis demonstrates that migrants, refugees and asylum seekers navigate and challenge not only sticky figurative borders, but also borders between different areas of law. The (non)interaction between these different areas of law may equally create or reinforce unequal human rights protection along gender lines. The law, across different areas and through the workings of diverse categories, definitions and standards, may thus work as a border-reinforcer.